Relative Price Convergence in Russia - De Masi, Paula (International Monetary Fund, 1995)
Following price and exchange rate liberalization, domestic consumer prices in Russia moved closer to market levels. This paper quantifies the magnitude of the associated relative price changes. It also shows that relative price variability has been positively correlated with inflation. It is further established that convergence toward international relative and absolute price levels is far from complete, and that geographical price dispersion within Russia has declined since early 1992 but remains fairly high